2003
DOI: 10.2981/wlb.2003.003
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting trapping success of red fox Vulpes vulpes, stone marten Martes foina and pine marten M. martes in France

Abstract: Trapping records are often used to monitor long-term trends of small carnivore populations. However, many factors, not related to abundance, may affect capture rates. In this study, we examined whether trapper experience, trapping effort and trapping methods significantly affect capture rates of red fox Vulpes vulpes, stone marten Martes foina and pine marten M. martes. Data were col lected from 58 trappers (35,774 trap-nights) in a 660-km2 study area during one trapping season. The main trapping methods used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Trapping efficiencies were highest for Collarum® (5.6-18.8 foxes per 1,000 trap-nights) and Belisle® (3.1-24.2 foxes per 1,000 trap-nights) (Muñoz-Igualada et al 2008). In France, Ruette et al (2003) obtained efficiencies of 1.2-17.9 foxes per 1,000 trap-nights and 0-31.7 foxes per 1,000 trap-nights, using neck or leg snares, respectively. Efficiencies calculated for Australia and US using different kind of snares varied from a minimum of 2.1 to as much as 21.6 foxes per 1,000 trap-nights (Litvaitis et al 1984, Meek et al 1995, Bubela et al 1998, Fleming et al 1998, Shivik et al 2005.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Trapping efficiencies were highest for Collarum® (5.6-18.8 foxes per 1,000 trap-nights) and Belisle® (3.1-24.2 foxes per 1,000 trap-nights) (Muñoz-Igualada et al 2008). In France, Ruette et al (2003) obtained efficiencies of 1.2-17.9 foxes per 1,000 trap-nights and 0-31.7 foxes per 1,000 trap-nights, using neck or leg snares, respectively. Efficiencies calculated for Australia and US using different kind of snares varied from a minimum of 2.1 to as much as 21.6 foxes per 1,000 trap-nights (Litvaitis et al 1984, Meek et al 1995, Bubela et al 1998, Fleming et al 1998, Shivik et al 2005.…”
Section: Discussionmentioning
confidence: 97%
“…Efficiency obtained in this study falls within the ranged observed by other authors in Europe using similar devices. Ruette et al (2003) argues trapping efficiency is affected by fox density, habitat type, the device used, but also by trapper experience in setting devices. Ferreras (2007) found that cage-trapping efficiency in Spain could range from 3 to 10 foxes per 1,000 trap-nights.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this study, trapper experts can assist with the on ground validation o f model results and link habitat change to population abundance in the form of trapping records (Smith et al 1984, Ruette et al 2003. Professional experts may provide a more general perspective on the habitat requirements o f individual species.…”
Section: Resultsmentioning
confidence: 99%
“…Expert-based wildlife studies may serve as an alternative to empirical-based research, particularly when the cryptic behaviour o f many furbearer species makes them difficult to study (Ruette et al 2003). Where empirical data are lacking, expert knowledge can provide useful insights on cumulative impacts and their influence on the distribution and abundance of furbearers.…”
Section: Introductionmentioning
confidence: 99%